On optimization of manufacturing of a step-down DC-DC converter to increase integration density of elements - E. L. Pankratov (Institute of Advanced Engineering and Science, 2021)
We consider the possibility to increase the field-effect transistor's density in a switched-capacitor step-down DC-DC converter. Based on this approach we analyzed the manufacturing of the converter in a heterostructure with a special structure. Some specific sections of the heterostructure must be doped by ion implantation or by diffusion. After this procedure optimized annealing has been done. We also obtained conditions for decreasing mismatch-induced stress value in this heterostructure. An analytical approach for the analysis of heat and mass transport in multilayer structures has been introduced. The approach gives a possibility without crosslinking of solutions on interfaces between layers, taking into account (i) spatial variation of parameters of considered processes; (ii) temporal variation of parameters of considered processes; (iii) nonlinearity of considered processes; and (iv) mismatch-induced stress.